Platelet serotonin in systemic sclerosis. - Klimiuk, P S (1989)
Platelet serotonin concentrations were measured in 43 patients with systemic sclerosis, in 11 patients with primary Raynaud's phenomenon, and in 38 normal controls. Patients with the CREST variant (calcinosis, Raynaud's phenomenon, oesophageal dysmotility, sclerodactyly, telangiectasia) had significantly lower platelet serotonin concentrations than normal controls. Patients with diffuse systemic sclerosis had normal platelet serotonin concentrations. In patients with CREST treatment with ketanserin, a specific serotonin antagonist, normalised platelet serotonin concentrations. These data provide further evidence suggesting that in systemic sclerosis, particularly the CREST variant, there is widespread platelet activation.